2019
DOI: 10.1111/cei.13332
|View full text |Cite
|
Sign up to set email alerts
|

A study of 51 subtypes of peripheral blood immune cells in newly diagnosed young type 1 diabetes patients

Abstract: Type 1 diabetes (T1D) results from autoimmune destruction of insulinproducing beta cells in pancreatic islets. Various immune cell populations are involved in disease development and natural course. However, to our knowledge, so far there are no comprehensive comparative investigations of all main immune cell populations and their most important subsets at the onset of disease. Therefore, in the current study, we analyzed 51 peripheral blood immune cell populations in 22 young T1D patients and in 25 age-matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 47 publications
8
39
0
Order By: Relevance
“…Alterations within CD19 + B cell subsets were only found in patients with HT despite that autoantibodies are also present in T1D, GD and AD. Previous studies addressing peripheral B cells in T1D and GD have reported that frequencies were similar compared to HC (32)(33)(34) or that functional responses toward autoantigens were changed (35,36).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Alterations within CD19 + B cell subsets were only found in patients with HT despite that autoantibodies are also present in T1D, GD and AD. Previous studies addressing peripheral B cells in T1D and GD have reported that frequencies were similar compared to HC (32)(33)(34) or that functional responses toward autoantigens were changed (35,36).…”
Section: Discussionmentioning
confidence: 95%
“…Most studies addressing NK cells in T1D have focused on their cytotoxic function, whereas studies investigating the phenotype of cell subsets are limited (52,53). It has been recently shown that children with newly diagnosed T1D had reduced frequencies of CD16 + CD56 dim and CD16 − CD56 dim NK cell subsets than HC (32). We have previously reported that multiple autoantibody-positive children, who later progressed to T1D, had higher frequencies of two CD8 + CD16 + CD56 dim NK cell subsets than autoantibody-negative individuals (18).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have described how T1D development is associated with changes in various peripheral blood circulating cell populations, and their asset might be associated with clinical and age-related differences in T1D patients [13][14][15][16]. It has been shown that in T1D subjects, the number of natural killer (NK), dendritic (DC), and T cell subsets is significantly altered compared to controls [17]. Moreover, the immunological profile significantly changes over time in T1D, and a specific peripheral immune cell signature can be associated with worsening disease [18].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study that examined a variety of immune cell subsets and cellular molecules in newly diagnosed children with T1DM found that the level of memory-regulatory T cells (mTreg) decreased after the appearance of clinical symptoms and aTreg and Th17 cells were significantly elevated in the first year of onset (the remission phase often occur) (15). The mTregs were also noted to be positively correlated with C-peptide in T1DM patients (16). Evidence of the obvious dynamic changes in Tregs in the different stages of remission phase suggested that the immune response during the remission phase was most likely related to the frequency and function of Tregs.…”
Section: Immune Cellsmentioning
confidence: 99%
“…The number of mononuclear cells also decreased after the onset of T1DM and reached the nadir in the first year (15). These changes of the immune cells in peripheral blood suggest an active extravasation to target tissues, probably contributing to the downregulation of the autoimmune response (16).…”
Section: Immune Cellsmentioning
confidence: 99%